MODERN ASPECTS OF GIARDIASIS DIAGNOSIS AND TREATMENT - D. V. Usenko; S. Yu. Konanykhina (Вопросы современной педиатрии)
Giardiasis is one of the most common parasitic invasions. Parasitizing the intestine, Giardia disrupt the structure and function of the small intestine, leading to recurrent or persistent clinical manifestations, as a rule, combining pain, dyspeptic and asthenoneurotic symptoms. Signs are similar to those of other variants of the pathology of gastroduodenal zone, intestine, biliary passages that makes clinical diagnosis almost impossible. A rational use of available diagnostic tests, as well as a strict adherence to the approved recommendations for giardiasis treatment in children allows to avoid the disease overdiagnosis and to increase therapy efficiency.